Are We Doing Enough? Assessing the Needs of Teachers in Isolated Schools with Students with Oppositional Defiant Disorder in Mainstream Classrooms - McLean, Fiona; Dixon, Roselyn (Australian and International Journal of Rural Education, 2010)
The Vinson report (2001) into public education highlighted the growing incidence of behavioural problems within the NSW public school system. One disorder that is currently causing particular concern is Oppositional Defiant Disorder (ODD) as the outcomes for students with ODD who do not receive intervention are dire. Barcalow (2006) claims that without intervention these behaviours may progress, sometimes rapidly, towards delinquency and incarceration. ODD has such a negative impact on classroom life and the working conditions of teachers and students that it needs urgent early intervention. The disorder does not only impact on the individual student, it impacts negatively on the other students, school staff and the learning environment. However, the area is not well-researched particularly from the viewpoint of the teachers who are in rural and isolated school in New South Wales. This qualitative research study examined the experiences of four teachers in two isolated rural schools in NSW who are currently teaching students with ODD. It examines the degree to which behaviours, of students with ODD impact on their own learning and socialisation skills and how this, in turn affects the teachers' ability to teach. Participant teachers indicated experiencing higher levels of stress when teaching students with ODD in isolated communities.